THU0216 Safety and Effectiveness of Adalimumabmethotrexate for The Treatment of Polyarticular Juvenile Idiopathic Arthritis (PJIA): Strive Registry. (15th July 2016) - Ruperto, N.; Lovell, D.J.; Wallace, C.; Toth, M.; Foeldvari, I.; Bohnsack, J.; Milojevic, D.; Rabinovich, E.; Kingsbury, D.; Marzan, K.; Quartier, P.; Minden, K.; et al.
Abstract : Background: JIA is the most common chronic inflammatory rheumatic diseases of childhood. Due to their long-term safety and efficacy, biologic disease modifying antirheumatic drugs (DMARD) are commonly necessary for control of pJIA patients (pts). Objectives: To evaluate 6-year (y) safety and 2 y effectiveness profile of Adalimumab with or without methotrexate (ADA±MTX) when used in current clinical practice for the treatment of moderately to severely active pJIA. Methods: This is a 6 y interim analysis of an ongoing, multicenter, non-interventional, observational registry of pts with moderately to severely active pJIA with up to10 y safety follow-up. Included pts are treated with either ADA±MTX or MTX alone as part of their routine clinical care enrolled in the US, EU, and Australia. MedDRA observational adverse events (AEs) were recorded from the first day in the registry through last contact, irrespective of the duration of registry treatment. Effectiveness was assessed by 27-joint juvenile arthritis disease activity score (JADAS27), based on CRP. Results: As of January 2014, enrollment was complete. As of June 1, 2015 cut-off date, 846 pts (543 in ADA±MTX and 303 in MTX groups) were treated in the registry. There were 39 pts who rolled over from the MTX to the ADA±MTX arm. At registry entry mean pJIA disease duration was 1.4 y and 3.7 y for MTX and ADA±MTX arms, respectively. At baseline (BL), mean AJC71 was 5.8 and 5.3 for MTX and ADA±MTX arms, respectively, and Childhood Health Assessment Questionnaire Disability Index (CHAQ-DI) was 0.6 for both arms. At data cutoff, the mean duration of study exposure was 1.81 y and 2.15 y for MTX and ADA±MTX arms, respectively. Overall, 206 pts (68%) in the MTX and 216 pts (39.8%) in the ADA±MTX arms discontinued registry drug through 6 y. The main reasons for registry drug discontinuation for the MTX arm: pts required additional therapy (32.3%), other (11.9%), lack of efficacy (10.9%), AEs (8.3%), or pts achieved JIA remission (7.6%), and for ADA±MTX arm: lack of efficacy (16%), lost to follow-up (7.2%), other (5.9%), and AEs (5.3%). Frequencies and rates of treatment-emergent AEs were similar to those reported for observational AEs (Table ). There were no reports of deaths, malignancies, opportunistic infections, active TB, oral candidiasis, or CHF. Mean JADAS27 (CRP) improved from 12.2 at BL to 9.7, 5.2, 4.4, 3.5, 2.2 at months 1, 6, and 12, 18, 24 for pts in the MTX and from 11.8 at BL to 7.0, 4.-2, 4.2, 3.6, 3.9 in the ADA±MTX arms, respectively (observed data). Conclusions: Overall, ADA±MTX was well-tolerated in these pts with pJIA with no new safety signals. Discontinuations from the registry drug were relatively high through 6 y, but greater in the MTX only arm. Acknowledgement: AbbVie sponsored the study & contributed with PRINTO & PRCSG to the analysis, review, and approval of the abstract. Xiaolei Leahy & Ashish Deshmukh of AbbVie contributed to the research. Medical writing support was provided by Gaurav Patki, PhD, of AbbVie. Disclosure of Interest: N. Ruperto Grant/research support from: AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfgroupaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Phgroupaceuticals., Employee of: GASLINI Hospital, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, Janssen Biologics B.V., MedImmune, Roche, and Wyeth/Pfizer, D. J. Lovell Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UBC, Xoma, and Genentech, Speakers bureau: Wyeth Pharmaceuticals, and served on data and safety monitoring boards for Amgen and Forest Research, C. Wallace Grant/research support from: Pfizer and Amgen, Consultant for: Amgen and Novartis., M. Toth: None declared, I. Foeldvari Consultant for: AbbVie and Novartis, J. Bohnsack Consultant for: Novartis, D. Milojevic Consultant for: Genentech and Novartis, E. Rabinovich Grant/research support from: UCB Pharma, Janssen Research & Development, LLC, Hoffmann-La Roche Inc., and AbbVie, D. Kingsbury Grant/research support from: AbbVie, K. Marzan Grant/research support from: AbbVie., P. Quartier Grant/research support from: AbbVie, Novartis, Consultant for: AbbVie, Novartis, K. Minden Grant/research support from: Pfizer and Abbvie, Consultant for: Pfizer, Abbvie, Roche/Chugai, Novartis, Medac and Pharma-Allergan., E. Chalom Speakers bureau: AbbVie, G. Horneff Grant/research support from: AbbVie, Pfizer, and Roche, Speakers bureau: AbbVie, Novartis, Pfizer, and Roche, R. M. Kuester Grant/research support from: AbbVie Inc. and Wyeth/Pfizer, J. Dare Grant/research support from: AbbVie, AstraZeneca, Bristol-Myers Squibb, Horizon Pharma, Medac, Pfizer, Roche, and UCB, M. Heinrich Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, H. Kupper Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, J. Kalabic Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, A. Martini Grant/research support from: AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Pharmaceuticals, Employee of: GASLINI Hospital, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, and MedImmune., H. I. Brunner Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Boehringer-Ingelheim, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UCB, and Genentech, Speakers bureau: Genentech Pharmaceuticals.